Mesoporous Silica and Zno@Sio2 as Adsorbents for Crystal Violet Dye Removal from Aqueous Solutions - Sameer H. Kareem (Journal of Global Pharma Technology, 2016)
Sol-gel method was used to prepare two samples of mesoporous Silica (mSiO2) and zinc oxide- mesoporous silica (ZnO@mSiO2) in the presence of HydroxycetylHydroxy ethyl Diamonium Chloride (dehyquart) surfactant as template. The two adsorbents prepared were characterized by nitrogen adsorption-desorption, XRD and AFM techniques. The results show that the mSiO2 sample has a mesopores in the range 2- 8 nm with a high degree of ordering of the porous structure, while Zn@SiO2 sample has pore distribution in the range 2-50 nm. The adsorption ability of the two adsorbents to removal of Crystal Violet (CV) dye from aqueous systems has been studied using a batch experiments method to measure the adsorption as a function of contact time and adsorbent dose at the temperature 293 K. Adsorption isotherms were fitted with the Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich models and the results show a best fitted for the two adsorbents, and the adsorption processes were physical adsorption type. The kinetic data were analyzed and found to match well with pseudo-second order kinetic model.Keywords: Mesoporous silica, Crystal Violet, Zn@SiO2, Adsorption isotherm.